2016
DOI: 10.1038/gt.2016.87
|View full text |Cite
|
Sign up to set email alerts
|

Late responses to adenoviral-mediated transfer of the aquaporin-1 gene for radiation-induced salivary hypofunction

Abstract: We evaluated late effects of AdhAQP1 administration in five subjects in a clinical trial for radiation-induced salivary hypofunction (http://www.clinicaltrials.gov/ct/show/NCT00372320?order=). All were identified as initially responding to human aquaporin-1 (hAQP1) gene transfer (Baum et al, 2012). They were followed for 3-4 years after AdhAQP1 delivery to one parotid gland. At intervals we examined salivary flow, xerostomic symptoms, saliva composition, vector presence and efficacy in the targeted gland, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 38 publications
(73 reference statements)
1
43
0
Order By: Relevance
“…The phase 1 clinical trial reported some success using an Aquaporin-1-expressing adenovirus. 15 , 16 Aquaporin-1 is a water channel not normally expressed in salivary ductal epithelium and was hypothesized to increase salivary fluid flow from the surviving undamaged ductal cells post-IR. 34 Our proof-of-principle in vivo study using AdNRTN before IR is based on the hypothesis that providing neurotropic support for the parasympathetic neurons will allow improved salivary function and regeneration of surviving epithelial progenitors after IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase 1 clinical trial reported some success using an Aquaporin-1-expressing adenovirus. 15 , 16 Aquaporin-1 is a water channel not normally expressed in salivary ductal epithelium and was hypothesized to increase salivary fluid flow from the surviving undamaged ductal cells post-IR. 34 Our proof-of-principle in vivo study using AdNRTN before IR is based on the hypothesis that providing neurotropic support for the parasympathetic neurons will allow improved salivary function and regeneration of surviving epithelial progenitors after IR.…”
Section: Discussionmentioning
confidence: 99%
“…The study confirmed that gene therapy is feasible in humans to potentially increase fluid secretion and relieve xerostomia experienced by patients after IR. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…The most studied is the adenovirus transfer of the human aquaporin-1 gene (hAQP1), which encodes a water channel protein involved in the osmotic movement of water in radiation-surviving salivary duct epithelial cells in the damaged gland. The strategy proved to be safe and effective in a phase I/II clinical study in humans previously irradiated for HNC, showing an increase in the saliva flow rate and a reduction of xerostomia-related symptoms which can continue years after hAQP1 delivery [70,71]. Recently, a non-viral approach employing ultrasound-assisted AQP1 cDNAs transfer was successfully tested in an animal model, allowing multiple gene administrations to maintain elevated salivary flow as opposed to the viral vectors where only a single administration is possible [72].…”
Section: Xerostomiamentioning
confidence: 99%
“…More recent work on this topic has shown that beneficial effects can continue years after parotid gland delivery (Alevizos et al, 2017), while other studies have demonstrated that that AQP1 gene therapy can also restore fluid movement in a murine model of Sjögren’s syndrome (Lai et al, 2016). Together, these results indicate the feasibility and benefits of using AQP1 gene delivery for treating various salivary gland conditions; however, new delivery methods are warranted to minimize any risk for immune response with repeated administrations (Lowenstein et al, 2007).…”
Section: Areas Of Growthmentioning
confidence: 99%